Beginning of the Diplomatic Mission of the Ambassador of Spain J. M. Paez de la Cadena to the Russian Empire (1824—1825) - R. O. Reinhardt (Научный диалог)
The question of the periodization and establishment of the chronological framework of the first stage of the work of J.M. Paez de la Cadena as head of the Spanish embassy in St. Petersburg after the Restoration of the monarchy  in Spain in 1823 is considered. An analysis of the available materials, during which it was revealed that there was  no exact dating of accreditation and the assumption of office of the named diplomat as a full-fledged member of the diplomatic corps, was carried out. It is shown that a number of humanitarian studies date the beginning of his mission to 1825, while in Russian historical works this issue is poorly and lapidarily covered. In order to clarify this information, work with the documents of the state archives of Madrid and Seville was carried out. By analyzing the dispatches stored in the corresponding funds, which have not yet been put into circulation within the framework of the Russian scientific discourse, it was established that Paez de la Cadena arrived in St. Petersburg no later than 1824. It is proved that by the beginning of 1825 he had already arrived to the Russian capital and corresponded with the central office of the Foreign Ministry in Madrid. Key issues that this correspondence dealt with are highlighted.